Prevalence and clinical features of chronic critical illness in the elderly population in Turkey - Demirkıran, Hilmi; Uzunoğlu, Emine; Erdivanlı, Başar; Karadamar, Ulaş; Koç, Suna; Tomak, Yakup; Özmen, Mustafa; Almalı, Necat; Çağaç, Aydın; Çömez, Mehmet Selim; Tuncer, Mustafa; Tokur, Murat Emre; et al. (Güneş Kitabevi Ltd. Şti, 2020)
Objectives: The definition of chronic critical illness in the elderly has not yet been determined. The aim of the study is to determine the prevalence and clinical features of chronic critical illness in the elderly population in Turkey.Materials and Methods: Data from 16 intensive care units of public and private hospitals in Turkey were evaluated. Patients staying in the intensive care units for at least eight days between 2015 and 2017 and having at least one of the additional criteria were accepted as chronic critical illness and they were divided into two groups by age, those 65 and older and those under 65.Results: The chronic critical illness patient rate in the intensive care units was 10.7%. Of chronic critical illness patients in the intensive care units, 60.9% were 65 years of age and older, and the mortality rate of patients 65 years and older was 70%. The frequencies of ischemic stroke and sepsis, the number of patients with comorbidities, and the mortality rate were higher in patients over 65 years of age, while the frequency of traumatic brain injury, presence of a major wound, tracheostomy, length of hospital stay and cost of care were higher in patients under 65 years of age.Conclusion: We determined that prolonged mechanical ventilation, traumatic brain injury, tracheostomy and major wound presence in intensive care units patients 65 years and older increased hospital stay and costs. More work is needed to define chronic critical illness more clearly in elderly.
Keywords: Chronic Disease; Critical Illness; Intensive Care Unit; Aged; Turkey